2007
DOI: 10.1002/ibd.20051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the anti-tumor necrosis factor-α antibody infliximab on the ex vivo mucosal matrix metalloproteinase–proteolytic phenotype in inflammatory bowel disease

Abstract: The high expression of MMPs in patients with IBD suggests a role for these proteinases in the pathogenesis of this disease. Infliximab seems to induce a genotype-associated matrix protective phenotype, which may contribute to the observed therapeutic efficacy of this drug in IBD, particularly at the mucosal surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 50 publications
1
41
1
1
Order By: Relevance
“…This cytokine has pleiotropic effects in the bowel wall: it induces neoangiogenesis 40 ; activates macrophages to produce proinflammatory cytokines; favours Paneth cell death via necroptosis 41 ; augments apoptosis of intestinal epithelial cells 42 ; regu lates T cell apoptosis 40,43,44 ; and reduces production of tissue inhib itor of matrix metalloproteinases (MMPs) by fibroblasts to mediate tissue injury via activated MMPs 45 . Thus, anti TNF antibodies can suppress intestinal inflammation in IBD through several mechanisms.…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…This cytokine has pleiotropic effects in the bowel wall: it induces neoangiogenesis 40 ; activates macrophages to produce proinflammatory cytokines; favours Paneth cell death via necroptosis 41 ; augments apoptosis of intestinal epithelial cells 42 ; regu lates T cell apoptosis 40,43,44 ; and reduces production of tissue inhib itor of matrix metalloproteinases (MMPs) by fibroblasts to mediate tissue injury via activated MMPs 45 . Thus, anti TNF antibodies can suppress intestinal inflammation in IBD through several mechanisms.…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Indeed, experimental data suggest that inhibition of MMP-9 may be of benefit in future strategies in IBD therapy [29,65]. It has also been suggested that infliximab therapy can induce a genotype-associated matrix protective phenotype by downregulating MMP-9 activity, which may contribute to the therapeutic efficacy of this drug in IBD [66]. It has also been proposed that anti-TNF therapy may enhance the inhibitor TIMP-1 production, which may reduce MMP activity and facilitate wound healing [67].…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphism (SNP) analysis for MMP-2 À1306C4T and MMP-9 À1562C4T was performed by tetraprimer ARMS PCR, involving four oligonucleotide primers but no restriction enzymes, or RFLP-PCR, as described earlier (Meijer et al, 2006;Kubben et al, 2006a).…”
Section: Single-nucleotide Polymorphism Analysismentioning
confidence: 99%